Satisfaction with online teaching of medical statistics during the COVID‐19 pandemic: A survey by the Education Committee of the Italian Society of Medical Statistics and Clinical Epidemiology. (22nd July 2021) - Rota, Matteo; Peveri, Giulia; Fanelli, Margherita; Torelli, Lucio; Rocchi, Marco BL; Specchia, Claudia
Abstract: On May 2020, after 2 months of online teaching with no face‐to‐face lectures, the Education Committee of the Italian scientific Society of Medical Statistics and Clinical Epidemiology conceived an online survey to assess satisfaction of Italian academics of medical statistics with online teaching and remote exams. This survey highlighted teachers' perceptions as well as opportunities and limitations of online teaching of medical statistics, biostatistics, and epidemiology. Although 61% of Italian academics of medical statistics declared to be favorable to provide online teaching of medical statistics, biostatistics, and epidemiology in the future, we recognize that distance education cannot substitute the unique value of teaching and knowledge exchange that could only be transmitted through a personal interaction between students and teachers. These indications may be useful to improve the quality of the teaching process in the future.